2018
DOI: 10.1016/j.ajpath.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Derived Indole Metabolites Promote Human and Murine Intestinal Homeostasis through Regulation of Interleukin-10 Receptor

Abstract: Interactions between the gut microbiota and the host are important for health, where dysbiosis has emerged as a likely component of mucosal disease. The specific constituents of the microbiota that contribute to mucosal disease are not well defined. The authors sought to define microbial components that regulate homeostasis within the intestinal mucosa. Using an unbiased, metabolomic profiling approach, a selective depletion of indole and indole-derived metabolites was identified in murine and human colitis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
276
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(322 citation statements)
references
References 53 publications
5
276
1
2
Order By: Relevance
“…These biologic activities were PXR-dependent. Alexeev et al reported that IPA was decreased in the serum of UC patients, with levels negatively associated with disease activity, and also in the serum and colons of SPF mice following DSS-induced colonic injury (71). Likewise, IPA is decreased in feces of patients with CD (51).…”
Section: Tryptophan Metabolites (Indoles)mentioning
confidence: 99%
See 1 more Smart Citation
“…These biologic activities were PXR-dependent. Alexeev et al reported that IPA was decreased in the serum of UC patients, with levels negatively associated with disease activity, and also in the serum and colons of SPF mice following DSS-induced colonic injury (71). Likewise, IPA is decreased in feces of patients with CD (51).…”
Section: Tryptophan Metabolites (Indoles)mentioning
confidence: 99%
“…Likewise, IPA is decreased in feces of patients with CD (51). Alexeev et al showed that E. coli metabolites of tryptophan induced expression of the IL-10 receptor subunit (IL10R 1 ) in colon cancer-derived T84 epithelial cells (71). GF mice monoassociated with E. coli WT K12 had elevated cecal levels of indoles and increased colonic epithelial IL10R 1 expression, while E. coli K12 deleted for the tryptophanase A gene had negligible cecal indole concentrations and no induction of colonic IL10R 1 gene expression over GF levels.…”
Section: Tryptophan Metabolites (Indoles)mentioning
confidence: 99%
“…Therefore, in order to maintain good health, controlling gut environment balance may be effective to maintain a good health status in humans. Recent studies have also found that the gut microbiota produces a large variety of metabolites such as short‐chain fatty acids (SCFAs) (Flint et al ., ; den Besten et al ., ), trimethylamine (Wang et al ., ), indole metabolites (Rothhammer et al ., ; Alexeev et al ., ), vitamins (LeBlanc et al ., ), polyamines (Kibe et al ., ) and secondary bile acids (Wahlström et al ., ). These molecules play important roles to maintain good health and suppress onset of various diseases in the host.…”
Section: Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…Mechanistically, microbiota can directly modify tryptophan metabolism via de novo synthesis of 5-HT [394]. The microbiota can also metabolize tryptophan into a number of bacterially derived indole metabolites that act at the aryl hydrocarbon receptor, resulting in immunoregulation and protection of the mucosa from damage [6, 217, 238]. Furthermore, microbial-derived SCFA is able to indirectly promote the production of 5-HT from epithelial cells in the gut [340].…”
Section: Underlying Mechanismsmentioning
confidence: 99%